An ELECTRE III based consensus‐reaching process to improve a collective solution. (9th April 2020) - Alvarez, Pavel Anselmo; Morais, Danielle Costa; Leyva López, Juan Carlos; de Almeida, Adiel Teixeira
Abstract: Group decision making (GDM) is a very important process to reach a collective solution with a certain level of consensus. When a collective solution is generated by the aggregation of individual solutions, the group members can feel some disagreements with the collective solution. The GDM process proposed in this paper is a framework that supports decision makers to reach a collective solution with a high level of consensus. The procedure includes two manners to carry out the GDM to reach a collective solution. An interesting aspect is the individual agreement and collective agreement increase in each round of the decision process. The results show that a collective solution is generated, and the convergence of the consensus is reached.